PO 8567 Association of polymorphism rs 73885319 of the APOL1 gene and resistance/susceptibility to trypanosoma brucei gambiense. (24th April 2019) - Erick, Mwamba Miaka; Lejon, Veerle; Ilboudou, Hamidou; Solano, Philippe
Abstract : Background: In Central Africa, human African trypanosomiasis (HAT) or sleeping sickness is caused by Trypanosoma brucei gambiense ( T.b gambiense ). Classically, the disease is characterised by an early haemolymphatic phase (stage 1) followed by a meningo-encephalitic phase (stage 2) leading to neurological disorders and death if left untreated. However, field observations suggest that infection by T.b gambiense may result in a great diversity of clinical outcomes ranging from rapid progressions into stage 2, to asymptomatic infections that can last for years or even spontaneous cure in the absence of treatment. The determinants of this clinical diversity are not known but might have their origin both in the parasite (genetic variability) and in the host (individual susceptibility to disease). This study in the Democratic Republic of the Congo aimed at examining the association between the rs73885319 polymorphism of the APOL1 gene and resistance/susceptibility to T. b gambiense . We genotyped the APOL1 gene polymorphism in a total of 257 people comprised of 90 patients, 119 endemic controls and 48 seropositives. The analysis of the results has not shown any significant differences between HAT patients, controls and seropositives. Our results seem to suggest that the G allele of the rs 73885319 polymorphism of the APOL1 gene is not associated to resistance or susceptibility to infection.